2020
DOI: 10.1126/sciadv.abd1951
|View full text |Cite
|
Sign up to set email alerts
|

Selective valorization of lignin to phenol by direct transformation of C sp2 –C sp3 and C–O bonds

Abstract: Phenol is an important commodity chemical in the industry, which is currently produced using fossil feedstocks. Here, we report a strategy to produce phenol from lignin by directly deconstructing Csp2–Csp3 and C–O bonds under mild conditions. It was found that zeolite catalyst could efficiently catalyze both the direct Csp2–Csp3 bond breakage to remove propyl structure and aliphatic β carbon–oxygen (Cβ–O) bond hydrolysis to form OH group on the aromatic ring. The yield of phenol could reach 10.9 weight % with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 61 publications
0
49
0
Order By: Relevance
“…[108] Very recently, Jiang and co-workers conducted a process for the preparation of phenols from lignin by directly depolymerizing Csp2À Csp3 bonds under mild conditions. [109] This work further opens an advanced approach and provides a sustainable strategy for obtaining phenolic compounds from lignin. Therefore, the production of AA from biomass-derived phenolic compounds represents a comparatively important opportunity and challenge for the chemistry industry.…”
Section: Preparation Of Adipic Acid From Phenolic Compoundsmentioning
confidence: 89%
“…[108] Very recently, Jiang and co-workers conducted a process for the preparation of phenols from lignin by directly depolymerizing Csp2À Csp3 bonds under mild conditions. [109] This work further opens an advanced approach and provides a sustainable strategy for obtaining phenolic compounds from lignin. Therefore, the production of AA from biomass-derived phenolic compounds represents a comparatively important opportunity and challenge for the chemistry industry.…”
Section: Preparation Of Adipic Acid From Phenolic Compoundsmentioning
confidence: 89%
“…Thus, a more efficient and sustainable strategy, that involves the utilization of biomass as feedstock to economically produce phenol, is highly desirable. Lignin is the most abundant renewable source composed of phenolic aromatic units present in Nature and represents a promising substrate for the green synthesis of phenols [10] …”
Section: Introductionmentioning
confidence: 99%
“…Lignin is the most abundant renewable source composed of phenolic aromatic units present in Nature and represents a promising substrate for the green synthesis of phenols. [10] In recent years, organic chemists have taken a resolute step toward the production of phenolic derivatives with tailored physicochemical properties. [11] Therefore, a wide variety of synthetic methodologies that allow the selective functionalization of the whole phenolic scaffold have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31] Recently, it was reported that zeolites showed remarkable performance in the selective elimination of the alkyl group, generating phenol and propylene as desired products, which achieved the utilization of the aromatic nucleus and side chains in lignin. [32][33][34][35] So, there are two important issues to realize the valorization of lignin: (1) developing effective strategies to achieve the breakage of C-C bonds; (2) transforming the aromatic nucleus and side chains in lignin to valuable compounds to improve the atom economy.…”
Section: Introductionmentioning
confidence: 99%